Using Radar Imagery Data to Determine Mixed Forests’ Characteristics - Viktor Sidorenkov; Iuliia Achikolova; Daniil Astapov; Oleg Ryabtsev (Environmental Sciences Proceedings, 2022)
Implementing inventory in remote and hard-to-reach forests is rather challenging. This study develops methods for identifying the qualitative and quantitative characteristics of mixed forests using Sentinel-1 imagery. The relationships between standing volume, forest density, age, and number of trees and radar survey indicators are revealed. The results are compared with forest inventory materials for a part of the study area. For most stands, there is a similarity in the standing volume and forest density definition. The study demonstrates that it is possible to identify quantitative and qualitative forest characteristics using radar survey data.